Pengaruh Pengetahuan Keuangan Dan Kontrol Diri Internal Terhadap Perilaku Manajemen Keuangan Syariah pada Pelaku UMKM Kecamatan Binjai Barat - Amelia Putri; Sugianto Sugianto (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
Individually owned, productive companies known as micro, small, and medium enterprises (MSME) are now flourishing in Indonesia. This study aimed to investigate the impact of internal locus of control and financial knowledge on the financial management behavior of MSME actors in West Binjai District. Due to several internal and external reasons that do not assist MSME in West Binjai District, this industry is unable to flourish because of a lack of knowledge about financial management. Primary data types are used in this quantitative research style. There are 100 UMKM when utilizing the Quota Sampling technique to determine the sample from the 228 MSME industries. Multiple linear regression analysis is used in this study to test the instrument. The results of the research conducted show that financial knowledge has no effect on financial management behavior and internal locus of control effect on financial management behavior MSME actors in West Binjai.